The Electrical Properties of Lanthanide Doped Potassium Sodium Lithium Niobate Based Silicate Glass - Ploypailin Yongsiri; Suchinda Sattayapom; Wipada Senanon; Kamonpan Pengpat (My University, 2021)
In this work, the electrical properties of ferroelectric glass-ceramics in the system of 75((K 0.5 Na 0.5 ) 0.94 Li 0.06 ) 1-x Er x NbO 3 - 25SiO 2 (75KNLNxEr - 25SiO 2 ) with x varying between 0.005-0.01 mol% have been investigated. The Er 2 O 3 is a lanthanide element that was found to promote the electrical and optical properties in many materials. The data from XRD pattern showed that the prepared glass-ceramics contained crystals of KNLNxEr solid solution, and the crystallite size slightly increased when increasing heat treatment temperature. For dielectric constant and dielectric loss at room temperature, the maximum values of about 304 at 1MHz with a dielectric loss below 0.01 was found in glass-ceramics without Er 2 O 3 dopant. The dielectric value can be raised to 1750 in glass doped with 0.005 mol% of Er 2 O 3 when the measurement temperature is increased. Finally, the oxidation states of glass-ceramics confirm by XANES showed that Er 2 O 3 dopant was Er trivalent cations, and the erbium ions were not precipitated in oxide form.
Keywords: Ferroelectric and Piezoelectric Materials; Glass properties and applications; Microwave Dielectric Ceramics Synthesis